ICT4Ag: Changing perceptions - Speer, Mark (Technical Centre for Agricultural and Rural Cooperation, 2013)
The session on ‘Capacity development, gender and ICTs in agriculture' stressed the importance of involving all stakeholders, including men and the larger family unit, in initiatives to improve women's access to ICTs.